State immunity and sovereignty of States the collection in international civil relations - Тімашова, Вікторія Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The problem of studying modern trends of state immunity in international private relations today is extremely urgent for the world community of states. State because of objective historical facts, and the uniqueness of its nature and due to its properties such as sovereignty and immunity, holds a special place in the modern, broadly international relations. Most scientists both domestic and Russian rightly believe that legal relations arising in the interaction of state and foreign entity, it is mediated by norms of international private (not public) law. state in the process of interaction of private international law concerning property relations (ie diagonal relations on the one hand - the state, the second – foreign private companies or citizens) occupies a special place, which is significantly different from other members of the legal status of legal - legal and individuals. This is due primarily to the fact that the state is simultaneously the bearer of ownership and the highest state authority in the country. To this is added a number of objective and subjective reasons, namely: 1) relationships to characterize the nature of the state elements such as territory, population, government); 2) the possible presence of political foundations in contracts between the state and a foreign entity; 3) if the state of immunity. Since the state as a subject of international law is sovereign and independent, they participate in international relations on an equal footing, regardless of differences between them in any objective characteristics (size of the territory, the level of economic development, population, availability of minerals etc.). Nevertheless, understanding the scope of the doctrine of state sovereignty in international law today is a philosophical and controversial issue. According to features views of scientists on this issue emerged two main concepts: 1) sovereignty - absolute characteristics, always characterized the state and not subject to restriction; 2) the sovereignty of the state in the international legal sense is limited. Because nowadays there is no single global practice of regulating matters related to the application of the concept of state immunity, the burden rests with the national legislation of States. It is helpful to track and summarize trends in the evolution of state immunity doctrine and practice of the most developed countries in this area.